A avaliação institucional participativa e os espaços políticos de participação construídos,reinventados,conquistados na escola - de Sordi, Mara Regina Lemes; Bertagna, Regiane Helena [UNESP]; da Silva, Margarida Montejano (FapUNIFESP (SciELO), 2016)
This article considers the Participatory Institutional Evaluation (AIP) as an important counter-regulatory resource that expresses constructive reaction of different actors towards the achievement of social quality of public schools. The article analyzes the powers,limits and challenges faced by the existing collegiate bodies (School Council) and the alternative space proposed by the Participatory Institutional Evaluation (Self Evaluation Commission),based on the experience of the Municipal Education of Campinas/SP,as part of a research conducted at the Centre of Education-OBEDUC/CAPES. The coordination of the progressive forces of school and society,which is opposed to the advances of corporate reformers,demands the existence of qualification of social spaces characterized by critical and plural dialogue among social actors so they can think,negotiate and decide important issues in a collective way,benefiting the children´s right to have a socialquality public education.
The participatory institutional evaluation and the participation of political spaces constructed,reinvented,and achieved at school
Keywords: Committee for assessment; Participatory institutional assessment; School council